Bank Financing and Firm Growth: The Role of Islamic Bank Financing - Al-Rdaydeh, Mahmoud; Muhammad, Joriah; Ibrahim, Haslindar (International Journal of Economics and Financial Issues, 2019)
The study examined the influence of Islamic and/or conventional bank financing on the growth of firms. The data were based on 113 firms in a Middle East country – Jordan – that implemented a dual-banking system from 2007 to 2016. The finding revealed that the implementation of either type of bank financing, be it Islamic and/or conventional, affect the growth of the firms. The study observed that Islamic bank financing had a more significant effect on the growth of the firms. Following the results of this study, stakeholders, managers, and investors are expected to change their views on Islamic bank financing, which is currently viewed as a part of religious practice. It may lead to the utilization of Islamic bank financing by firms. It should be noted that this study is one of the first empirical studies on the impact of Islamic bank financing on the growth of firms. Keywords: interest-free credit facility; Islamic finance; conventional loan; firm growth; panel data. JEL Classifications: G 30; G32; C23 DOI: https://doi.org/10.32479/ijefi.8278